Bring a Friend : Strengthening Women’s Social Networks and Reproductive Autonomy in India - Anukriti, S (Washington, DC : World Bank, 2022)
This paper experimentally tests whether enabling individuals to incentivize others to socialize with them can strengthen social networks and improve well-being. The paper examines family planning access for women in India, who tend to be socially isolated and for whom peer support may overcome intrahousehold constraints. Enabling women to jointly visit a clinic with other women not only increased social ties and strengthened peer engagement, but also increased clinic visits and contraceptive use. Moreover, this intervention was more effective in improving reproductive autonomy of women who faced greater intrahousehold opposition than an intervention that only improved women’s own access to the clinic.